Description of Helicoconis tatricus sp. n. (Neuroptera, Coniopterygidae) from Slovakia (Central Europe) and key for determination of all Palaearctic species of subgenus Helicoconis - Vidlička, Ľubomír (Zootaxa, 2014)
A new species of dustywings, Helicoconis tatricus sp. n., is described from the foothills of the Tatra Mountains in Slovakia. The new species differs from other species of the subgenus Helicoconis by structure of male genitalia—unfurcated styli and wide and short apophyses. The key for determination of all Palaearctic species of the subgenus Helicoconis is added and the distribution of Palaearctic species is discussed.